Modus of art in poertry of Mykhaylo Dray-Khmara (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article deals with the modes of art and the problems of the relation between the semantics of Mykhaylo Dray-Khmara's poetic text and non-textual reality. The poetry included in the Prorosten collection is analyzed. It is noted that the tragic and elegiac artistic modality is intertwined in M.Dray-Khmara's poetic texts, but the elegiac mode of art prevails ("She put silk crosses", "She lives until today", "the August eve was chilled ..." and others). The elegiac hero of the poet from his subjective "corner" admires not himself, not his subjectivity, but his life, his irreversibility, his individual insistence in the objective picture of the universal life arrangement.It has been investigated that in the poetry of M. Dray-Hmara the semantic factor dominates; its main task is to create new meanings, unique semantic complexes, which are still based on the phenomena of the real world and are with them in certain relationships.The poetics of the Ukrainian neoclassic have been analyzed and it is deduced that it is what semantic poetics stands for, on the basis of which the creation of "new meanings" is created.
Keywords: tragedy; elegance; art; modality; poetry; poetics